Influencer Dynamics in the Digital Culinary Landscape: Unveiling the Impact and Engagement Strategies of @kulinersby on Instagram - Syafira Devani Putri; Gagas Gayuh Aji (Management Analysis Journal, 2024)
The study aims to analyze social media, which has emerged as a medium influencing perceptions and behaviors. In the dynamic landscape of digital media, social platforms have fundamentally reshaped how individuals navigate and express their identities, ushering in a new era of online influence. At the forefront of this transformative wave are social media influencers, whose ability to craft compelling personas within specific niches has garnered them significant sway over audience perceptions and behaviors. This qualitative study delves deep into the intricate methods employed by influencers to shape their online presence, with a particular focus on Instagram and the renowned account @kulinersby. Through meticulous observation and content analysis, this research unveils the nuanced strategies utilized by influencers, including the strategic deployment of authentic storytelling, visually captivating content, and interactive engagement tactics. By shedding light on these key findings, this study not only offers valuable insights into the influential role of influencers but also provides a deeper understanding of the evolving dynamics between influencers and their audiences in the digital age.